2020
DOI: 10.3390/pharmaceutics12030224
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin–Loaded Human Serum Albumin Submicron Particles: Preparation, Characterization and In Vitro Cellular Uptake

Abstract: Doxorubicin (DOX) is an effective anthracycline antibiotic drug which is commonly used in a broad range cancer therapy. However, due to dose depending side effects and toxicity to non-cancerous tissues, its clinical applications are restricted. To overcome these limitations, human serum albumin (HSA) has been investigated as a biocompatible drug delivery vehicle. In this study, human serum albumin submicron particles (HSA-MPs) were fabricated by using the Co-precipitation–Crosslinking–Dissolution technique (CC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
(49 reference statements)
2
15
0
Order By: Relevance
“…In this study, the adsorption of NS to HSA-MnCO 3 particle varied and depended on the concentration and fabrication steps. These results indicated that non-sericin substance with poor water solubility can be entrapped into the HSA-MnCO 3 particle via electrostatic and hydrophobic interactions which is similar to the results of doxorubicin loaded HSA-MnCO 3 particle [16]. The HSA-MnCO 3 templates were incubated with different concentrations of NS.…”
Section: Particle Preparationsupporting
confidence: 70%
See 2 more Smart Citations
“…In this study, the adsorption of NS to HSA-MnCO 3 particle varied and depended on the concentration and fabrication steps. These results indicated that non-sericin substance with poor water solubility can be entrapped into the HSA-MnCO 3 particle via electrostatic and hydrophobic interactions which is similar to the results of doxorubicin loaded HSA-MnCO 3 particle [16]. The HSA-MnCO 3 templates were incubated with different concentrations of NS.…”
Section: Particle Preparationsupporting
confidence: 70%
“…This could be suggestive of a common uptake mechanism of the albumin receptor. Similarly, a study involving doxorubicin revealed that it was loaded into HSA-MPs, uptaken by the A549 cells and then localized in the cell lysosomal compartment [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Albumin represents an appealing protein-based macromolecular carrier due to its non-toxicity, non-immunogenicity, biocompatibility, easy incorporation of various drugs, and ability to bind with proteins [21,82,83]. Albumin nanoparticles have been shown to exhibit enhanced affinity for anti-cancer drugs, including paclitaxel [84][85][86][87] (FDAapproved nanoformulation as Abraxane ® /ABI-007 (Celgene) [88]), doxorubicin [87,[89][90][91][92], docetaxel [93][94][95][96], tacrolimus [87,97], and curcumin [98,99].…”
Section: Albuminmentioning
confidence: 99%
“…Specifically, stimuliresponsive delivery systems have been created to target the acidic pH and/or hypoxic environment characteristic of tumor cells [210] (Figure 5). In this respect, polymeric nanoparticles have been investigated as carriers towards various tumor cells, including breast [44,[211][212][213], colon [91,[214][215][216][217], gastric [169,[218][219][220], liver [116,221,222], bladder [46,223], skin [224,225], lung [36,92,226], prostate [94,[227][228][229], and ovarian [230][231][232] cancer cells (Table 2). In this respect, polymeric nanoparticles have been investigated as carriers towards various tumor cells, including breast [44,[211][212][213], colon [91,[214][215][216][217], gastric [169,[218]…”
Section: Drug Deliverymentioning
confidence: 99%